An Appraisal of Research Designs Used to Investigate the Information Content of Audit Reports. - Bailey, William T. (The Accounting Review, 1982)
ABSTRACT: To draw conclusions about the information content of audit reports, one must isolate the effects of information conveyed specifically by audit-report components of aggregate signals. To do so, the information conveyed by other components of the aggregates must be controlled. This paper argues that, for most types of audit reports, the necessary control cannot be exercised with security-price research methods Accordingly, some inappropriate inferences have been drawn about the information content of certain types of opinions. Research strategies to provide and implement the necessary control are suggested.